ANALYSING FACILITIES AND ACCESSIBILITY AND IMPACTS OF THE TOURIST’SATISFATION IN DOLLI BUNGAEJA, MAROS, INDONESIA - Sitti Fatimah Julianty; Kurnia Yusniar Rahman (Politeknik Pariwisata Makassar, 2025)
This study aims to analyze perceptions of facility adequacy and accessibility and their influence on visitor satisfaction levels at the Dolli Bungaeja tourist attraction in Maros Regency, South Sulawesi. The focus of the study includes evaluating facilities such as toilets, parking areas, prayer rooms, seating areas, and information boards, as well as accessibility, which includes road conditions, ease of directional signage, and the availability of public transportation and private vehicles. Data collection was conducted through questionnaires, in-depth interviews, and direct observation at the location. A mixed qualitative and quantitative approach was used to reveal visitor experiences and measure satisfaction objectively. The results of the study show that most visitors consider the existing facilities to be adequate with fairly good maintenance, especially in terms of cleanliness. However, there is a need to improve facilities by adding toilets and expanding the parking area to accommodate the increasing number of visitors. In terms of accessibility, the road conditions leading to the location still need to be improved to ensure a comfortable and safe journey. Some visitors also considered the directional signs and information boards at the location to be unclear, making it difficult for new visitors. Easy access to tourist sites has been shown to contribute positively to visitor satisfaction, which in turn increases the likelihood of visitors returning and recommending the destination to others. The study recommends improving road infrastructure, developing more comprehensive supporting facilities, and optimizing digital information and promotion. The involvement of the local community is very important in destination management to maintain cleanliness, preserve the environment, and improve services. In addition, the development of new tourist attractions such as ecotourism activities, enrichment of local culture, and improvement of supporting facilities such as gazebos and rest areas will add to the destination's appeal. Managers are also advised to improve training for staff so that they are able to provide excellent and responsive service to visitors' needs. Support from the local government and cooperation with relevant stakeholders are also key factors in implementing sustainable tourism development strategies. With these steps, Dolli Bungaeja is expected to not only become a competitive and comfortable destination but also be able to provide sustainable economic contributions and empower the community socially. This study provides a comprehensive overview of the factors that determine visitor satisfaction and relevant development strategies based on questionnaire data and interviews that have been thoroughly analyzed.